2018
DOI: 10.1002/ejoc.201800143
|View full text |Cite
|
Sign up to set email alerts
|

α‐Hydroxy‐Tetrazoles as Latent Ethynyl Moieties: A Mechanistic Investigation

Abstract: This article focuses on the dehydration of α‐hydroxy‐tetrazoles, leading to tetraazafulvenes and then to vinylic carbenes that rearrange into ethynyl moieties through the Fritsch–Buttenberg–Wiechell rearrangement. Each step of this sequence was scrutinized, either by examination of the substrate and/or dehydrating agent scope, or through AM1 calculations, in order to understand the limiting step of this process. This underrated transformation appears to be a viable alternative to existing methods used for tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Scheme 8 Total synthesis of combretastatin A4 via a HAT Couty et al recently reported a new route to HATs using trimethylsilyl (TMS)-cyanohydrins 22, which could be readily prepared from the reaction of aldehydes with TMSCN in the presence of a catalytic amount of triethylamine (Scheme 9). 16 Treatment of 22 with TMSN3/Bu2SnO (cat) followed by desilylation in an acidic medium afforded aldehyde-HATs 5 in one pot with good overall yields. This procedure can be performed under mild conditions, making it an efficient and practical method for the synthesis of 5 from aldehydes.…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
See 3 more Smart Citations
“…Scheme 8 Total synthesis of combretastatin A4 via a HAT Couty et al recently reported a new route to HATs using trimethylsilyl (TMS)-cyanohydrins 22, which could be readily prepared from the reaction of aldehydes with TMSCN in the presence of a catalytic amount of triethylamine (Scheme 9). 16 Treatment of 22 with TMSN3/Bu2SnO (cat) followed by desilylation in an acidic medium afforded aldehyde-HATs 5 in one pot with good overall yields. This procedure can be performed under mild conditions, making it an efficient and practical method for the synthesis of 5 from aldehydes.…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
“…of LiCN were required when aldehydes were employed. 13a In a previous report, County indicated that the transformation from cyanohydrin derivatives could be highly substratedependent, 16 because the reaction of cyanocarbonates or CMs (cyanomesylates) with TMSN3/Bu2SnO (cat) produced poor yields of the corresponding alkynes. On the other hand, Harusawa et al recently reported that the reaction of benzylic CPs 9 with sodium azide in the presence of Et3N .…”
Section: Tetrazole Fragmentation From Cpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we demonstrated that treatment of 1 with carbodiimides triggers a sequence of dehydration and fragmentation to generate alkylidenecarbene 2 , and the products of their reactions under mild, nonbasic conditions (Scheme ). In this previous study, a two-step procedure was developed to access substrates 1 , namely, addition of 1-allyl-5-lithio-1 H -tetrazole ( 3 ) to ketones and aldehydes 4 and catalytic de- N -allylation of 5 (Scheme , A ). Despite its high efficiency, this approach requires low reaction temperatures to prevent decomposition of 3 and a discrete N- deprotection step.…”
Section: Introductionmentioning
confidence: 99%